Permodelan Sistem Informasi Pembelian dan Penjualan Berbasis Website - Sanriomi Sintaro (PT. SNN MEDIA TECH PRESS, 2022)
The purpose of designing a website-based system is to provide information and services easily and quickly. Users can quickly search for product, service, or other content information through an easy-to-use interface. The modeling of a website-based buying and selling information system is carried out by looking at sales transactions and purchases of goods that occur displayed in graphic form so that leaders can quickly find out the total number of buying and selling transactions that occur in the company. And the process of inputting sales and purchase data does not require manual recording as occurs in the procedures that have been running, so as to reduce errors in inputting sales and purchase data that will cause company losses. The results of testing the functionality of the system on the pages contained in the website-based purchase and sales information system model concluded that the test results were in accordance with the expected results in the black box testing questionnaire with a value of 100%.